Direct Comparison of Neck Pinhole Dual-Tracer and Dual-Phase MIBI Accuracies With and Without SPECT/CT for Parathyroid Adenoma Detection and Localization. (June 2015) - Heiba, Sherif I.; Jiang, Manli; Rivera, Javier; Genden, Eric; Inabnet, William; Machac, Josef; Kostakoglu, Lale
Abstract : Introduction: There is uncertainty about accuracies of dual-phase (DP) and dual-tracer (DT) parathyroid scintigraphy with the newly added SPECT/CT. Although SPECT/CT was shown to be helpful in parathyroid adenoma (PA) localization, it may not have optimal resolution as pinhole. This study directly compared diagnostic accuracies and confidences of various imaging protocols on same patients. Patients and Methods: One hundred fifty-five patients with pathologically confirmed diagnosis were included. Pinhole DP, pinhole DT, pinhole DP SPECT/CT, pinhole DT SPECT/CT, and SPECT/CT with only pinhole-delayed MIBI (D) were reviewed for accuracies and certainties of PA diagnosis/localization. Parathyroid adenomas were classified as clearly or unclearly distinguishable from thyroid. Furthermore, the contribution of pinhole DP to pinhole DT SPECT/CT was assessed. Results: Of 153 PAs, the correct diagnosis/localization was significantly higher by pinhole DT SPECT/CT than pinhole DP SPECT/CT, SPECT/CT D, pinhole DT alone, and DP alone. Parathyroid adenomas were clearly more distinguished from thyroid in pinhole DT than DP with/without SPECT/CT. Consequently, PA diagnosis certainty was higher in pinhole DT than DP, whereas PA localization certainty was higher in both with SPECT/CT. In pinhole DT SPECT/CT, the pinhole DP addition confirmed diagnosis/localization of only 24 uncertain PAs. Conclusions: In this large patient group, the accuracy and certainty of PA diagnosis/localization were higher in pinhole DT SPECT/CT than all other parathyroid scintigraphy protocols. Pinhole DT better identified PA than pinhole DP, whereas SPECT/CT improved PA localization in both protocols. Pinhole DP showed limited contribution and thus should be only considered when PA diagnosis/localization is uncertain by pinhole DT SPECT/CT.